(untitled) (Bangladesh Agronomy Journal, 2020)
An experiment was conducted at the Agronomy research field, Sher-e-Bangla Agricultural University, Dhaka from November, 2015 to March, 2016 to study the performance of wheat-mustard intercropping as influenced by different row ratios. Ten treatments were included in the study as, T1 (sole wheat), T2 (sole mustard), T3 (wheatmustard in 2:1 rows), T4 (wheat-mustard in 3:1 rows), T5 (wheat-mustard in 4:1 rows), T6 (wheat-mustard in 5:1 rows), T7 (wheat-mustard in 2:2 rows), T8 (wheat-mustard in 3:2 rows), T9 (wheat-mustard in 4:2 rows) and T10 (wheat-mustard in 5:2 rows). The experimental result indicatedthe significant variations of wheat yield by the wheatmustard intercropping system. The highest seed yield of wheat (3.4 t ha-1) was obtained from T1 (sole wheat) that identical with T4 (wheat-mustard in 3:1 rows) and similar with T9 (wheat-mustard in 4:2 rows). Wheat yield gradually decreased with increasing mustard rows. The lowest seed yield (1.87 t ha-1) was obtained from T7 (wheat-mustard in 2:2 rows) which was statistically similar to T8 (wheat-mustard in 3:2 rows). The highest wheat equivalent yield (5.03 t ha-1) was obtained from T4 (wheat-mustard in 3:1 rows). Treatment T4 (wheat-mustard in 3:1 rows) produced the highest LER (1.45). Economic analysis of the different treatments showed that the highest gross return (Tk. 120250.0 ha- 1), the highest net return (Tk. 61178.0 ha-1) and BCR (2.04) from T4 (wheat-mustard in 3:1 rows). Therefore, present study suggest that wheat and mustard intercropped in 3:1 rows showed the most compatible in respect of yield advantage and economic gain. Bangladesh Agron. J. 2019, 22(2): 161-169